Association of Physical Fitness Participation with Cognitive Function and Balance among the Elderly in Denpasar - Lanawati; Rina Listyowati; Raden Ayu Tuty Kuswardhani (Universitas Udayana, 2015)
Background and purpose: Aging is known to cause cognitive impairment and body imbalance. Studies have found that physical exercise helps to delay such depreciation. The purpose of this study was to assess the relationship between participation in physical fitness and cognitive function and body balance among the elderly in Denpasar. Methods: Study was cross sectional, involving 60 elderly who were categorised into those who participated in physical exercise and those who did not, using proportional stratified random sampling. MoCa-Ina was used to determine the level of cognitive function and Romberg Test was applied to determine body balance. Data were analysed using chi-square and logistic regression tests. Results: The proportion of normal cognitive function among elderly who did and did not participate in physical fitness were 80% and 20%, respectively. Similarly, proportions of normal body balance among the elderly who did and did not participate in physical fitness were 86.7% and 20.0% respectively. These differences were statistically significant. In logistic regression analysis, it was shown that the variables affecting cognitive function were participation in physical fitness and in a hobby, and variables that affected body balance were participation in physical fitness and disease history. Conclusion: Participation in physical fitness was associated with cognitive function and body balance among elderly.